2020
DOI: 10.1177/0363546520906406
|View full text |Cite
|
Sign up to set email alerts
|

Video Confirmation of Head Impact Sensor Data From High School Soccer Players

Abstract: Background: Recent advances in technology have enabled the development of head impact sensors, which provide a unique opportunity for sports medicine researchers to study head kinematics in contact sports. Studies have suggested that video or observer confirmation of head impact sensor data is required to remove false positives. In addition, manufacturer filtering algorithms may be ineffective in identifying true positives and removing true negatives. Purpose: To (1) identify the percentage of video-confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
59
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 14 publications
2
59
1
Order By: Relevance
“…10,34,35,40,41 Recent technological advances have enabled the development of head impact sensors to estimate the head impact exposure of human subjects in vivo. 31 A wide variety of head impact sensors is currently available, such as instrumented helmets (e.g., GForceTracker), 5,7,26 headbands (e.g., SIM-G), 18,32,43 mouthguards (e.g., MIG) 16,46 and skin patches (e.g., xPatch). 23,28,33 Increasingly, research studies have used such technology to collect head impact data in sports, commonly American football.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,34,35,40,41 Recent technological advances have enabled the development of head impact sensors to estimate the head impact exposure of human subjects in vivo. 31 A wide variety of head impact sensors is currently available, such as instrumented helmets (e.g., GForceTracker), 5,7,26 headbands (e.g., SIM-G), 18,32,43 mouthguards (e.g., MIG) 16,46 and skin patches (e.g., xPatch). 23,28,33 Increasingly, research studies have used such technology to collect head impact data in sports, commonly American football.…”
Section: Introductionmentioning
confidence: 99%
“…47 Furthermore, field studies have evaluated the accuracy of sensors to measure head impact exposure using video analysis. 7,16,28,32,33 Such previous research has identified that the absence of observer and/or video confirmation of sensor-recorded events to remove false positives may result in substantial overestimation of head impact exposure. 7,18,32,33 Although filtering algorithms attempt to remove false positives in an automated fashion, some investigations suggest such approaches are limited and not a valid replacement for observer and/or video confirmation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 In addition to low uncertainty kinematics estimates, qualitative video confirmation of head impacts has gained traction in the past few years as being very useful to pair with impact monitoring data, 6,8,14,17,[23][24][25]32,42,44,46,47,63 Bartsch et al, 4,5 Kieffer et al, 39 Bartsch et al, 3 Bartsch et al, 2 . 18,60,73 An emerging benefit of such video reviews is that objective visible signs (VS) such as motor incoordination, lying motionless, impact seizure, among others can be documented (Bruce et al BJSM 8 NHL).…”
Section: Introductionmentioning
confidence: 99%